Molecular examination of GH gene deletion in familial growth hormone deficiency. - S. Lekhakula (2018)
The human growth hormone gene (GH gene) from nine members of a family with familial growth hormone deficiency was examined. The patients were diagnosed as having growth hormone deficiency clinically and by response to hormonal treatment. PCR amplification was carried out using total DNA extracted from leukocytes. The flanking regions of the GH gene which are highly homologous were amplified by one pair of primers. PCR products of 1900 bp and 1919 bp were obtained. By using the combination of restriction enzymes BgII, HaeII and SmaI to digest these PCR products, the various sizes of GH gene deletion can be detected. None of the possible deletions was found in these patients and their relatives by either PCR or Southern blot analysis.